2015
DOI: 10.1111/cen.12864
|View full text |Cite
|
Sign up to set email alerts
|

Follicular and endocrine dose responses according to anti‐Müllerian hormone levels in IVF patients treated with a novel human recombinant FSH (FE 999049)

Abstract: Objective To study the association between serum anti-M€ ullerian hormone (AMH) levels and follicular development and endocrine responses induced by increasing doses (5Á2-12Á1 lg/day) of a novel recombinant human FSH (rhFSH, FE 999049) in patients undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) in a GnRH antagonist protocol. Design Secondary analysis of a randomized controlled trial with stratified randomization according to AMH (lower stratum: 5Á0-14Á9 pmol/l; higher stratum: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…A subsequent dose-increase would recruit another wave of follicles that would therefore result in increased variability of follicle size by the end of stimulation. We observed that a lower starting rFSH dose reduced the proportion of follicles sized 12–19 mm at the end of stimulation in keeping with data using a novel human rFSH (39) and with our previous data (22). Furthermore, the need to increase the mean dose of rFSH by more than 5% of the starting dose reduced the proportion of follicles of 12–19 mm at the end of stimulation, and this was associated with 5 fewer mature oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…A subsequent dose-increase would recruit another wave of follicles that would therefore result in increased variability of follicle size by the end of stimulation. We observed that a lower starting rFSH dose reduced the proportion of follicles sized 12–19 mm at the end of stimulation in keeping with data using a novel human rFSH (39) and with our previous data (22). Furthermore, the need to increase the mean dose of rFSH by more than 5% of the starting dose reduced the proportion of follicles of 12–19 mm at the end of stimulation, and this was associated with 5 fewer mature oocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Dosing follitropin delta according to mass rather than bioactivity measured in rat is important as a result. This principle is being pursued in follitropin delta clinical development, with individualized dosing by mass optimized for each patient based on their AMH level and weight (11, 12). The differences between the pharmacology of follitropin delta and follitropin alfa also suggest that one should not be directly substituted for the other in one clinical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently follitropin delta has been described (FE 999049), the first recombinant FSH protein in clinical development that is expressed in a human cell line (PER.C6), with individualized dosing optimized based on each patient’s weight and anti-Mullerian hormone (AMH) level (10, 11, 12). In female volunteers, follitropin delta displayed distinct pharmacokinetics and pharmacodynamics, with higher exposure and lower serum clearance than follitropin alfa (13).…”
Section: Introductionmentioning
confidence: 99%
“…Individualised ovarian stimulation with follitropin delta relies on very narrow categories of AMH to stratify women to the appropriate gonadotropin dose to achieve a target ovarian response of 8–14 oocytes ( Arce et al , 2014 ; Bosch et al , 2015 ; Nyboe Andersen et al , 2017 ). That a large number of women would be classified differently if an alternative assay was used, in part reflects the small AMH categories that were used in the original dosing algorithm.…”
Section: Discussionmentioning
confidence: 99%